The Role of Legal Education in Improving Ecological-Legal Culture (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The increasingly severe environmental situation in the world poses serious questions for humanity. Reasonable reflection on them places various responsibilities on each of us today. The depletion of the ozone layer on our planet, the negative impact of unexpected climate changes, excessive air pollution, degradation of fertile soils, and the sharp decline in species of fauna and flora, which are leading to a decrease in biodiversity, require the world community to be extremely vigilant and aware of the environment. The shortage of clean drinking water has also become an acute problem. If the situation continues in this way, it is predicted that the world will face major environmental risks.